2013
DOI: 10.1002/app.39885
|View full text |Cite
|
Sign up to set email alerts
|

Effect of expandable graphite particle size on the flame retardant, mechanical, and thermal properties of water‐blown semi‐rigid polyurethane foam

Abstract: Different particle size of expandable graphite (EG) were incorporated into water‐blown semi‐rigid polyurethane foams (SPFs), which acted as the fire shield, in order to enhance the fire retardant properties. In this study, the particle size of EG was systematically varied from 70 µm to 960 µm. The effect of EG particle size on the density, mechanical properties, and thermal stability of SPFs was also investigated. Results showed that EG with smaller particle size showed almost no effect on the fire retardant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 24 publications
6
54
2
Order By: Relevance
“…The differences between 3D and T‐EVA/EG (10 wt%) materials could be explained by three factors: (1) the EG particles size, lower after 3D printing. These smaller EG particles lead to lower graphite expansion, to a less cohesive entangled network and thus to lower thermal protective performances (Figure C). (2) The higher porosity observed in the 3D printed materials might also decrease the cohesion of the entangled network, thus damaging the fire protective properties of 3D‐materials compared to T‐materials.…”
Section: Resultsmentioning
confidence: 99%
“…The differences between 3D and T‐EVA/EG (10 wt%) materials could be explained by three factors: (1) the EG particles size, lower after 3D printing. These smaller EG particles lead to lower graphite expansion, to a less cohesive entangled network and thus to lower thermal protective performances (Figure C). (2) The higher porosity observed in the 3D printed materials might also decrease the cohesion of the entangled network, thus damaging the fire protective properties of 3D‐materials compared to T‐materials.…”
Section: Resultsmentioning
confidence: 99%
“…For example, boric acid can be bonded on EG surface by the silane coupling agent (KH550) . Finally, it has been confirmed that EG expansion volume and its particle size have the effects on the flame retardancy, mechanical properties, and thermal stability of polymer composites .…”
Section: Introductionmentioning
confidence: 94%
“…The HB test is a method which is generally applied to assess the extent and the linear burning rate of the horizontal combustion [21]. Table 4 summarizes the HB data of the neat EMB and brucite/EMB composites.…”
Section: Horizontal Burningmentioning
confidence: 99%